The Influence of Paddy Fields toward The Seasonal Herbaceous Wetland Ecosystem in Rawa Pening Lake - Desti Christian Cahyaningrum (Universitas Mataram, 2020)
Most of the tidal land in the lakeside of Rawa Pening is currently used for rice farming activities. This activity is thought to have negative impacts on seasonal herbaceous wetland ecosystem in this region. The study aimed to analyze the influence paddy fields toward the seasonal herbaceous wetland ecosystems in Rawa Pening Lake through an vegetation composition and structure approach. This study is a quantitative descriptive research with field observation method. Data of vegetation was collected using line intercept transect technique in the area widely of 625 m2 for each affected and unaffected ecosystem sample. Data analysis was performed by calculating the Sorensen Similarity Index (IS), the Margalef Diversity Index (R), the Shanon-Wiener Diversity Index (H'), the Dominance Index (C), and the Evenness Index (E). The results showed that there were differences in the composition and structure of vegetation on the two ecosystem samples, seen from the value of similarity index (IS) between both of them that included in the low criteria (39.85%). The results also showed that the Shanon-Wiener Diversity Index (H') and the Margalef Diversity Index (R) on the affected ecosystem sampleÃÂ (H' = 1,9834; R = 1,825) are lower when compared to the unaffected ecosystem sample (H'= 2,1297; R = 2,112). So it can be concluded that the existence of paddy fields has changed the composition and structure of vegetation and reduced the diversity of vegetation in the affected ecosystem. Based on these conclusions, it is recommended to construct a sustainable management system of paddy fields on Rawa Pening Lake's tidal land as the effort for natural ecosystems maintenance in this region, especially in the biodiversity and ecological services preservation.